The Role of Work Discipline in Mediating the Relationship between Leadership and Organizational Culture on Employee Performance at the Regional Office of the Ministry of Religion of North Sumatra Province - Ayu Alzahra, Hilda; Rahayu, Sri (PT. Multidisciplinary Press Indonesia, 2025)
This study aims to examine the direct and indirect effects of leadership and organizational culture on employee performance, with work discipline as a mediating variable. The study was conducted in 2025 at the Regional Office of the Ministry of Religious Affairs of North Sumatra Province, involving 65 respondents from a total of 185 employees selected through purposive sampling based on the Slovin formula. Primary data were collected using a questionnaire and analyzed using a quantitative-associative approach through the SEM-PLS method using the SmartPLS 3 application. The results of the analysis show that leadership and organizational culture have a positive and significant effect on work discipline, but do not directly affect employee performance. Conversely, work discipline has a significant effect on performance. Organizational culture is a dominant factor in shaping work discipline, while work discipline is the main determinant of performance. Indirectly, leadership and organizational culture affect performance through work discipline. This research model explains 72.6% of the variation in work discipline and 73.3% of the variation in employee performance.